Manajemen Pendidikan Inklusi pada Anak Berkebutuhan Khusus di SMA Muhammadiyah 10 Surabaya - Dewi Rahmawati Mustafa Kallu; Juli Amaliya Nasucha (Institut Nalanda, 2024)
The results of the research show that inclusive education for children with special needs at SMA Muhammadiyah 10 Surabaya follows the curriculum determined by the government, therefore every month a joint evaluation meeting is held regarding the learning process which is carried out every month. The teaching and learning process requires good preparation and planning, this is none other than to achieve learning objectives. Inclusive Education for Children with Special Needs is a phenomenon that we encounter in society. The author also found this phenomenon in the Muhammadiyah 10 High School Surabaya environment where many students used sign language when they were with friends who were speech impaired and when they met friends who were not speech impaired they used Indonesian.